Characteristics of invasive fungal infection in critical patients of the altitude with septic shock. - Tinoco-Solórzano, Amílcar (2023)
Introduction: In the ICU, 19% have fungi, 23% develop septic shock. Candida albicans the most frequent. The most commonly used antifungal is fluconazole. Objectives: In high altitude residents with septic shock (SS) we will describe: Characteristics, evolution and sensitivity of invasive fungal infection (IFI) and we will contrast them with those published at sea level. The study: Retrospective and transversal. We analyzed blood cultures of adults with SS and IFIs in an ICU at 3,250 meters of altitude, for 7 years. Findings: 123 samples. The IFIs increased 3.6 for candida albicans. Women with 74 years was frequent. BGN represented 52.88%, BGP 37.9% and fungi 9.22%. Candida albicans 79.67% with sensitivity greater than 90% for Voriconazole, Amphotericin B and Fluconazole. Conclusions: IFIs with SS were caused by candida albicans, IFIs increased, there is adequate sensitivity to antifungals. At high altitudes there is a higher frequency of females, higher average age, and good sensitivity to fluconazole.